Downcore color scan data from sediment core M144_5-6 from the central western Aegean Sea - Sven Pallacks; Patrizia Ziveri; Helen A Jannke; Chien-Hsiang Lin; Adam V Subhas; Eric Douglas Galbraith; Stefanie Kaboth-Bahr; Oliver Friedrich; André Bahr; Andreas Koutsodendris; Jörg Pross; Richard D Norris (PANGAEA, 2025)
The dataset contains a downcore color scan of Kasten Core M144 KC5-6 for each 1cm. The analysis was performed onboard the R/V Meteor using a A MINOLTA CM-700d hand-held spectrophotometer combined with a CM-A178 target mask (Ø 8 mm, with plate). Color data were reported in the CIELAB space using the L*a*b* system. To calibrate the spectrophotometer, a Konica Minolta White Calibration Cap CM-A177 and Zero Calibration Box CM-A182 were used. Spectral reflectance was measured over a wavelength spectrum from 400 to 700 nm. Low L* and a* values representing darker, organic rich layers were defined sapropel phases as discussed in Pallacks et al. (in review).
In: Pallacks, S et al. (2025): Fish otolith and planktic foraminiferal abundances and radiocarbon dates from sediment kasten core M144_5-6 in the central western Aegean Holocene [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974530